Natural Resources In Islamic-based Sustainable Development: A Case Study Of Negara Brunei Darussalam - Ramli, Raudha Md (2022)
The oil and gas industry is the main contributor to the national income and Gross Domestic Product (GDP) of Negara Brunei Darussalam. Brunei’s dependence on the oil and gas industry exposes the country to long-term economic risks such as the drastic reduction of global oil prices, which could threaten its sustainable development. Therefore, how can Brunei reduce its dependency on oil and gas resources? Seeing that Brunei has incorporated Islam into its national philosophy and its aspiration and vision of national development, how can this philosophy, aspiration, and vision be executed as part of Brunei’s development strategy to ensure the sustainability of the country’s natural resources? Furthermore, how then can Islam form the basis for Brunei’s development plan? To answer these questions, three research objectives were derived. The first objective is to identify the concept of natural resources that is in line with Brunei’s sustainable development. The second objective is to analyse the vital natural resources available for sustainable development in Brunei based on the context of the Malay Islamic Monarchy (MIB), Zikir Nation, and Brunei Vision 2035, while the third objective is to propose Islamic-based sustainable development strategies for Brunei. A qualitative-based case study framework was applied to collect three types of data: authentic sources, al-Qur’an and hadith; primary sources, semi-structured interviews; and secondary sources, published documents. The data was analysed using thematic content analysis.